(untitled) (Journal of the College of Basic Education, 2023)
A new ligand 4-methylbenzyl (2E)-2-[1-(pyridin-3-yl) ethylidene] hydrazinecarbodithioate (PE4MBHC) with nitrogen sulphur donor sequence was prepared from the reaction between 1-(pyridin-3-yl)ethanone (PE) and 4-methylbenzyl hydrazinecarbodithioate (4MBHC). Complexes of this ligand with Cu(II), Ni(II) and Zn(II) were synthesized and characterized using elemental analysis and various physicochemical techniques. The metal complexes were six coordinated and all the new compounds were tested against different bacteria and fungi and also against two breast cancer cells. All metal complexes showed moderate activity against microbes while copper and nickel shows strong activity against MCF7 and MDAMB231 respectively.